2023
DOI: 10.3389/frvir.2023.1067932
|View full text |Cite
|
Sign up to set email alerts
|

Is mixed reality technology an effective tool for retail? A vividness and interaction perspective

Abstract: There is increasing interest in studies analyzing the influence of technologies that integrate virtual and real-world components on consumer behavior. These technologies include augmented reality, virtual reality and mixed reality. Mixed reality is a user environment in which physical reality and digital content are combined in a way that enables interaction with and among real-world and virtual objects. In spite of previous works related with MR and retails spaces, little is known about how consumers respond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 89 publications
0
0
0
Order By: Relevance
“…The study also found that the perceived hedonic and utilitarian values of the shopping experience were heightened when MR was employed. This enhancement in the shopping experience translated into positive future purchase intentions and an improved emotional state among consumers (Gil-López, et al, 2023).…”
mentioning
confidence: 97%
“…The study also found that the perceived hedonic and utilitarian values of the shopping experience were heightened when MR was employed. This enhancement in the shopping experience translated into positive future purchase intentions and an improved emotional state among consumers (Gil-López, et al, 2023).…”
mentioning
confidence: 97%